Karakteristik Sosiodemografis dan Ketenagakerjaan Perempuan di Perkebunan Sawit, Provinsi Lampung - Anna Fatchiya; Asri Sulistyawati; Fredian Tonny; Mahmudi Siwi; Julio Adisantoso; Tri Budiarto; Kunandar Prasetyo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
As a contributor to the country's economy, the oil palm plantation sector is also expected to absorb female workers who have often been marginalized. This study tries to reveal the extent of the role of women in the process of managing oil palm plantations in Penawar Tama District, Tulang Bawang Regency, Lampung Province. The study was conducted quantitatively on 121 female respondents with the status of: independent smallholders, family camps, casual daily laborers and employees of oil palm companies. The results showed that activities in the management of oil palm plantations were still dominated by men. The role of women in this case is only involved in the process of fertilization and leaf maintenance. Regarding the division of labor in the household, the majority of women have a double workload where domestic work such as cooking, washing and cleaning the house is the main job that must be done by women.